Music and social inclusion international research and practice in complex settings - Odena, Oscar (SEMPRE studies in the psychology of music, 2023)
How do we develop social inclusion through musical activities? What is the power of music in enhancing individual inclusion, group cohesion, and cross-community work in post-conflict environments? How can we investigate social music programmes and interventions? This comprehensive volume offers new research on these questions by an international team of experts from the fields of music education, music psychology, ethnomusicology, and community music. The book celebrates the rich diversity of ways in which learners of all ages participate in social music projects in complex settings. Contributions focus broadly on musical and social processes, considering its conceptualisation and practices in a number of contexts. The authors examine how social music projects can be fostered in complex settings, drawing examples from schools and community settings. These criticalchapters will inspire readers to think deeply about social music interventions and their development. The book will be of crucial interest to educators, policymakers, researchers, and students, as it draws on applied research from across14 countries, of which ten are in the Global South